Ethnic Dynamics in Northern Senatorial Zone, Taraba State, Nigeria: An Inter-Group Perspective - Ali, Bello; Lawal, Salihu (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
This paper, titled